Significance of Neutrophil Gelatinase-Associated Lipocalin as a Biomarker for the Diagnosis of Diabetic Kidney Disease: A Systematic Review and Meta-Analysis - Peng He; Ming Bai; Jin-ping Hu; Chen Dong; Shiren Sun; Chen Huang (Karger Publishers, 2020)
Background: Neutrophil gelatinase-associated lipocalin (NGAL) is a promising marker for the diagnosis of diabetic kidney disease (DKD), but its utility is currently debated. This meta-analysis aims to evaluate the diagnostic value of NGAL for DKD. Method: MEDLINE, Embase, Cochrane Library, CNKI, and CBM databases were searched up to April 13, 2019. In bivariate random-effect models, the diagnostic performance of NGAL for DKD was assessed using pooled estimates of sensitivity, specificity, likelihood ratio, diagnostic odds ratio, and hierarchical summary receiver-operating characteristic analysis. Results: Nineteen studies were eligible for the meta-analysis. Serum NGAL had a pooled sensitivity and specificity of 0.79 (95% confidence intervals [CI] 0.60-0.91) and 0.87 (0.75-0.93) (7 studies, 1,238 patients). The pooled positive likelihood ratio (LR+) and negative likelihood ratio (LR-) were 5.97 (3.03-11.76) and 0.24 (0.11-0.51). For urine NGAL, the pooled sensitivity, specificity, LR+, and LR- were 0.85 (0.74-0.91), 0.74 (0.57-0.86), 3.26 (1.87-5.67), and 0.21 (0.12-0.35), respectively (10 studies, 1,369 patients). The pooled sensitivity and specificity for kidney disease in normoalbuminuric patients with diabetes was 0.90 (0.82-0.95) and 0.97 (0.90-0.99) for both serum NGAL and 0.94 (0.87-0.98) and 0.90 (0.81-0.96) for urine NGAL (4 studies, 221 patients). NGAL appeared to perform similarly in subgroup analysis. Conclusion: The meta-analysis has shown that NGAL may be useful for DKD classification and also has a potential diagnostic value for normoalbuminuric kidney disease. Large-scale prospective studies are required to clarify its role in the diagnosis and risk stratification of patients with DKD.